2002
DOI: 10.1002/dev.10061
|View full text |Cite
|
Sign up to set email alerts
|

Relative right versus left frontal EEG in neonates

Abstract: Although infants have been noted to have greater relative right or left frontal EEG as early as the neonatal period, other ways in which these newborns differ have not been reported. In this study, 48 newborns were divided on the basis of greater relative right versus greater relative left frontal EEG to determine whether these groups differed in other ways at the neonatal period including behavior, physiology, and biochemistry. We also were interested in whether these EEG patterns were related to any prenatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 34 publications
(23 reference statements)
1
14
0
Order By: Relevance
“…The preferred methodological approach was the fast-Fourier transform analysis, studied initially with fullterm neonates (Eiselt et al, 2001;Field et al, 2002;Ktonas et al, 1995;Lehtonen et al, 1998;Witte et al, 1997), followed by more recent reports in preterm infants (Eisalt et al, 1997;Holthausen et al, 2000;Kuhle et al, 2001;Myers et al, 1997;Sawaguchi et al, 1996;Schramm et al, 2000;Vanhatalo et al, 2002). Similar calculations, based primarily on assumptions of stationarity, were also described for specific neonatal and infant risk groups for sudden infant death syndrome (Schechtman et al, 1995), apnea (Schramm et al, 2000), hyperbilirubinemia (Gurses et al, 2002), white matter necrosis (Inder et al, 2003), and asphyxia (Hellström-Westas, 1992), applying power analyses to one particular physiologic behavior with little attention to the multiple neuronal networks that contemporaneously express state transitions.…”
Section: Automated Neonatal State Detection Strategiesmentioning
confidence: 99%
“…The preferred methodological approach was the fast-Fourier transform analysis, studied initially with fullterm neonates (Eiselt et al, 2001;Field et al, 2002;Ktonas et al, 1995;Lehtonen et al, 1998;Witte et al, 1997), followed by more recent reports in preterm infants (Eisalt et al, 1997;Holthausen et al, 2000;Kuhle et al, 2001;Myers et al, 1997;Sawaguchi et al, 1996;Schramm et al, 2000;Vanhatalo et al, 2002). Similar calculations, based primarily on assumptions of stationarity, were also described for specific neonatal and infant risk groups for sudden infant death syndrome (Schechtman et al, 1995), apnea (Schramm et al, 2000), hyperbilirubinemia (Gurses et al, 2002), white matter necrosis (Inder et al, 2003), and asphyxia (Hellström-Westas, 1992), applying power analyses to one particular physiologic behavior with little attention to the multiple neuronal networks that contemporaneously express state transitions.…”
Section: Automated Neonatal State Detection Strategiesmentioning
confidence: 99%
“…Henriques & Davidson, 1990) as well as infants of depressed mothers (e.g. Field, Diego, Hernandez-Reif, Schanberg & Kuhn, 2002) showed greater relatively right frontal EEG activation. A study investigating adults revealed that individuals with insecure attachment showed lower left frontal asymmetry (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Earlier investigations applied linear analyses to physiologic data sets without consideration of time-dependent nonlinear behaviors [33,[100][101][102][103][104][105][106][107] . Fast-Fourier transform was initially applied to studies of full-term neonates [108][109][110][111][112] followed by more recent reports in preterm infants [113][114][115][116][117][118][119][120][121][122] . These algorithms were also used to describe specific neonatal and infant risk groups, such as sudden infant death syndrome [123] , apnea [117,124] , hyperbilirubinemia [125] , white matter necrosis [126] , and asphyxia [127] .…”
Section: Computer-assisted Analyses Of Neonatal Eeg/sleep Represent Amentioning
confidence: 99%